Subjective and objective appearance of head and neck cancer patients following microsurgical reconstruction and associated quality of life: A cross-sectional study - Kansy, Julia Katharina; Hoffmann, Joachim; Alhalabi, Obada; Mistele, Nicole; Freier, Kolja; Mertens, Christian; Freudlsperger, Christian; Engel, Michael (Journal of cranio-maxillofacial surgery, 2018)
Purpose - Depending on the site and size of head and neck cancer, the disease affects patients' appearance and subsequently their quality of life. The aim of this study was to correlate subjective and objective evaluation of facial appearance and associated quality of life following ablative tumor surgery and microsurgical reconstruction. - Material and methods - A total of 99 patients with combined ablative and reconstructive microsurgical procedure for head and neck malignancy and seven patients with non-malignant disease were examined by three-dimensional (3D) (photogrammetry at least 6 months post-surgery and were evaluated by two-dimensional (2D) and 3D means for symmetry and facial proportions. Measurements were correlated with subjective reporting from the University of Washington Quality of Life Questionnaire and observer ratings. - Results - Of the 106 patients, three patients scored themselves as significantly disfigured (2.8%), 19 were bothered by their appearance (17.9%), 27 (25.5%) reported no change, and 57 (53.8%) reported minor changes in their appearance. On 2D evaluation, 10 patients (9.4%) showed severely abnormal facial proportions. On 3D analysis, 17 patients showed major asymmetry. There was a high correlation (0.67) between patient and observer subjective rating (p < 0.05). While 2D evaluation alone showed no significant correlation with subjective rating, 3D evaluation showed a moderate correlation (0.37; p < 0.05). The best results were achieved by combining 2D and 3D measurements (0.5; p < 0.05). Young female patients were most critical about their appearance. - Conclusion - Following combined ablative and microsurgical reconstructive procedures, patients have a realistic perception of their appearance compared with observer ratings and a combination of 2D and 3D objective evaluation.